What do Germans really think about health-nudges? - Krisam, Mathias; Maier, Mona; Janßen, Rebecca; Krisam, Johannes (BMC public health, 2021)
In recent years, policymakers have increasingly used behaviourally informed policies, including ‘nudges’. They have been implemented to produce desirable social outcomes such as healthier eating and physical activity. In Germany, a small research team at the Federal Chancellery acts as the central unit to promote the introduction of nudges in the design of public life. Despite this, the nudging concept itself as well as the understanding around it has not spread widely among German citizens. When reporting about the concept, German media is often very critical of the concept.
Gesehen am 28.07.2021